(untitled) (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2024)
The Anthropocene, a concept designating the geological era marked by human influence, has become a central subject for natural and social sciences in the 21st century. This study examines Alexander von Humboldt’s contribution to the conceptualization of human-nature interactions, positioning him as a precursor to the Anthropocene concept. Textual analysis of his travel account on Lake Valencia reveals Humboldt’s holistic ecological vision, integrating humans into the complex network of nature, contrasting with the dominant anthropocentric conceptions of the Anthropocene. This pioneering perspective enriches the history of ecological thought and demonstrates the relevance of Humboldt’s work in contemporary debates on the Anthropocene.